MODELAGEM DA CONTINUIDADE E DA DINÂMICA ESPACIAL DA ÁREA BASAL EM CLASSES DIAMÉTRICAS DE UM REMANESCENTE DE FLORESTA OMBRÓFILA MISTA - ROVEDA, Marcelo; FIGUEIREDO FILHO, Afonso; PELISSARI, Allan Libanio; GENÚ, Aline Marques; GRESPAN, Tiago (Brazilian Journal of Biometrics, 2018)
The study aimed evaluate dynamics and modeling of the stock spatial continuity in total basal area (m² ha-1) in different diametrical classes of a mixed ombrophilous forest remnant in the South of Brazil measured between 2002 and 2014. The total basal area stock was obtained through a continuous monitoring carried out in 400 georeferenced sampling units measuring 25 m x 25 m installed in 2002 and measured again in 2005, 2008, 2011 and 2014. Next, geostatistics was used to model the spatial continuity and punctual ordinary kriging was employed to generate thematic maps. The results obtained confirmed that the basal area continuity can be modeled and spatialized in 10|–20 and 20|–30 cm diametrical classes, while the pure nugget effect was observed in the remaining diameter classes on all occasions throughout the continuous monitoring. Also, the diametrical class and the forest dynamics tended to modify the form through which this structure is detected via geostatistical analysis, becoming directly related to the number and spatial distribution of the individuals.